PTH-220 Pregnancy in established home parenteral nutrition (HPN). (22nd June 2015) - Gashau, WJ; Nixon, E; Sutcliffe, K; Lal, S
Abstract : Introduction: There are few case reports of successful pregnancy in patients on Home Parenteral Nutrition (HPN). Most of the available literature focuses on acute, short-term PN use in hyperemesis gravidarum. We report five successful pregnancies on established HPN patients over a 30-year period in a national Intestinal Failure Unit. Method: HPN macronutrient and fluid regimes during pregnancy were determined by resting energy requirements with additional alterations influenced by maternal stressors, underlying medical condition, maternal weight gain and foetal growth measurements. Micronutrient alterations were guided by recommended daily allowances (RDA) already precedent in obstetric care, adjusted according to biochemical and haematological indices checked regularly throughout gestation. Results: The median time on HPN before pregnancy was 18 months (range 4–72). Two pregnancies presented late at 12 and 25 weeks gestation. Both were unplanned and one patient was on warfarin until 12 weeks gestation. No antenatal or postnatal anomalies were reported in this infant. Four out of five pregnancies reached full term, with one pre-term delivery at 30 weeks gestation. There were no documented cases of essential fatty acid or fat-soluble vitamin deficiency. In two cases, placentas were examined post-partum and showed no evidence of lipid deposition. Subsequent growth and development of all infants have been satisfactory. Median maternal weight gain was 5kg (range 1–5.5kg). Foetal measurements were deemed satisfactory in all pregnancies with birth-weights ranging between 10 th and 75 th centile for gestational age. All patients received a portion of their energy requirement from lipid emulsion. There were no documented catheter related infections during gestation or in the post-partum period. Two patients developed worsening liver enzymes on a background of Intestinal Failure Associated Liver Disease (IFALD). The first was attributed to increasing energy requirements during pregnancy and the second due to cholestasis of pregnancy. Both improved post-partum. Conclusion: All women of child-bearing age on HPN should be counselled about pregnancy. Ideally, it should be planned to allow appropriate monitoring. With appropriate support, pregnancy and delivery can occur uneventfully with minor adjustments needed in established HPN regimes to ensure adequate foetal growth. Disclosure of interest: None Declared.